2022
DOI: 10.1098/rspb.2022.1642
|View full text |Cite
|
Sign up to set email alerts
|

Ageing leads to reduced specificity of antimicrobial peptide responses in Drosophila melanogaster

Abstract: Evolutionary theory predicts a late-life decline in the force of natural selection, possibly leading to late-life deregulations of the immune system. A potential outcome of such deregulations is the inability to produce specific immunity against target pathogens. We tested this possibility by infecting multiple Drosophila melanogaster lines (with bacterial pathogens) across age groups, where either individual or different combinations of Imd- and Toll-inducible antimicrobial peptides (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Recently, using Drosophila lines with different combinations of knocked out AMP genes, the pathogen-specific roles of AMPs have been reported, where microbicidal activity against a particular pathogen depended mainly on a certain AMP, e.g., the Dpt gene family alone provided effective defense against Providencia rettgeri , drosocin contributed to defense against Enterobacter cloacae , whereas buletin (also encoded by the Dro gene) was effective against Providencia burhodogranariea [ 63 , 64 ]. In addition to these findings, it turned out that when considering the role of AMPs in Drosophila response to infection, age and sexual dimorphism should be taken into account given the documented strong differences in immune response at the basal level upon infection and during aging between sexes [ 65 , 66 ]. Hanson et al showed that Dpt expression was sufficient to protect young male flies against P. rettgeri ; however, Shit et al demonstrated that reintroduction of functional Dpt A and Dpt B (∆ AMPs +Dpt ) fully restored survival and decreased the P. rettgeri load only in young males but not in females or older males [ 63 , 66 ].…”
Section: Amps In Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, using Drosophila lines with different combinations of knocked out AMP genes, the pathogen-specific roles of AMPs have been reported, where microbicidal activity against a particular pathogen depended mainly on a certain AMP, e.g., the Dpt gene family alone provided effective defense against Providencia rettgeri , drosocin contributed to defense against Enterobacter cloacae , whereas buletin (also encoded by the Dro gene) was effective against Providencia burhodogranariea [ 63 , 64 ]. In addition to these findings, it turned out that when considering the role of AMPs in Drosophila response to infection, age and sexual dimorphism should be taken into account given the documented strong differences in immune response at the basal level upon infection and during aging between sexes [ 65 , 66 ]. Hanson et al showed that Dpt expression was sufficient to protect young male flies against P. rettgeri ; however, Shit et al demonstrated that reintroduction of functional Dpt A and Dpt B (∆ AMPs +Dpt ) fully restored survival and decreased the P. rettgeri load only in young males but not in females or older males [ 63 , 66 ].…”
Section: Amps In Agingmentioning
confidence: 99%
“…In addition to these findings, it turned out that when considering the role of AMPs in Drosophila response to infection, age and sexual dimorphism should be taken into account given the documented strong differences in immune response at the basal level upon infection and during aging between sexes [ 65 , 66 ]. Hanson et al showed that Dpt expression was sufficient to protect young male flies against P. rettgeri ; however, Shit et al demonstrated that reintroduction of functional Dpt A and Dpt B (∆ AMPs +Dpt ) fully restored survival and decreased the P. rettgeri load only in young males but not in females or older males [ 63 , 66 ]. Aging had negative effects on the fitness and pathogen clearance ability of Drosophila females but not males.…”
Section: Amps In Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the widespread occurrence of immunosenescence across the tree of life, including in insects [14], suggests the opposite—that is, a decline in immune function, and hence in parasite resistance with age [15,16]. In insects, studies have revealed that immunosenescence can manifest as excessive, overly reactive and less specific immune responses, without any notable improvement in survival [1719]. Furthermore, different components of the insect immune response (enzymatic versus cellular) can display distinct age-specific patterns [16].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the widespread occurrence of immunosenescence across the tree of life, including in insects [14], suggests the opposite; that is, a decline in immune function, and hence in parasite resistance with age [15,16]. In insects, studies have revealed that immunosenescence can manifest as excessive, overly-reactive and less specific immune responses, without any notable improvement in survival [17][18][19]. Furthermore, different components of the insect immune response (enzymatic versus cellular) can display distinct agespecific patterns [16].…”
Section: Introductionmentioning
confidence: 99%